The osteosarcoma immune microenvironment in progression: PLEK as a prognostic biomarker and therapeutic target - Yunpeng Zou; Yunpeng Zou; Jianning Kang; Shaopeng Zhu; Xuechen Ren; Zheng Li; Jiayao Niu; Xuanzhe Qin; Hongbo Li; Lu Xiang; Wei Jiang; Jiangbo Zhong; et al. (Frontiers in Immunology)
IntroductionOsteosarcoma (OS) is a malignant bone tumor with high metastatic potential and poor long-term survival. The tumor immune microenvironment and metabolic reprogramming are increasingly recognized as key drivers of OS progression, yet the molecular links between these systems remain unclear. This study aimed to identify immune-metabolic biomarkers in OS, focusing on pleckstrin (PLEK) as a potential regulatory hub.MethodsWe conducted differential expression and survival analyses using OS transcriptomic datasets and TCGA/GTEx data. Protein–protein interaction networks, GO/KEGG enrichment, and CytoHubba algorithms identified core hub genes. Tumor-infiltrating immune cells were profiled via TIMER. Single-cell RNA-seq (GSE162454) was used for immune and metabolic landscape mapping. PLEK was further validated by qRT-PCR and Western blot in OS samples, and its function assessed via siRNA knockdown in macrophages within TME co-cultured with OS cells. Cell proliferation, migration, and invasion assays evaluated phenotypic effects in OS cells.ResultsNine hub genes were identified, with PLEK significantly upregulated in OS tissues. High PLEK expression correlated with improved survival and increased infiltration of macrophages, dendritic cells, and CD4+ T cells. Single-cell analysis showed PLEK enrichment in macrophage-dominated clusters with active glycolytic and oxidative phosphorylation pathways. Downregulation of PLEK in macrophages enhanced OS cell proliferation, migration and invasion. These findings suggest PLEK is linked to a pro-immune, metabolically active microenvironment and may act as a tumor suppressor.DiscussionOur study identifies PLEK as a prognostic biomarker and functional regulator in OS. It promotes an immune-infiltrated, metabolically active tumor microenvironment and is associated with attenuated malignant phenotypes in vitro. These findings highlight PLEK as a promising target for immunometabolic modulation in OS.